DESIGN AND CONSTRUCTION OF GILLNET IN THE VILLAGE NIPAH PANJANG 2 SUBDISTRICT OF NIPAH PANJANG TANJUNG JABUNG TIMUR REGENCY PROVINCE OF JAMBI - Taufiqurrahman '; Irwandy Syofyan; T Ersti Yulikasari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in February 2017 in the Village Nipah Panjang 2, Subdistrict Nipah Panjang, Tanjung Jabung Timur Regency, Province of Jambi. The method used is to observe directly the fishing gear used by fishermen. This study aims to produce an Efficient gillnet fishing gear design through an assessment of the construction of gillnet used by fishermen. The principle of design theory uses the reference formula Sadhori (1984) and Fridman (1986). The results show that the construction of gillnet consists as webbing, upper main line, under main line, float line, sinker line, float, sinker I, sinker II and buoy. Based on the calculation of design formula was obtained distinguish of mesh size, spin of line, number of float and sinker, floats and sinker mounting distance. The spin direction used in the sample as Z-Z, while for the new design it is better to use the opposite spin direction such as Z-S or S-Z. The number of sample float is 701 pieces with a distance of 1 m (mesh size 3 inch) and 401 pieces with a distance of 1 m (mesh size 7 inch). While the recommended number of float is 1567 pieces with a distance of 45 cm (mesh size 3 inch) and 540 pieces with a distance of 75 cm (mesh size 7 inch). The number of sample sinker is 1556 pieces with a distance of 45 cm (mesh size 3 inch) and 160 pieces with a distance of 2,5 m (mesh size 7 inch). While the recommended amount of sinker is 1923 pieces with a distance of 36 cm (mesh size 3 inch) and 664 pieces with a distance of 60 cm (mesh size 7 inch). The number of buoy sample is 42 pieces (mesh size 3 inch) and 24 pieces (mesh size 7 inch). While the recommended buoy is 41 pieces (mesh size 3 inch) and 14 pieces (mesh size 7 inch)Keyword: Contruction, Design, Gillnet, Tanjung Jabung Timur